2008
DOI: 10.2478/s11756-008-0100-5
|View full text |Cite
|
Sign up to set email alerts
|

Elliptochloris bilobata var. corticola var. nov. (Trebouxiophyceae, Chlorophyta), a novel subaerial coccal green alga

Abstract: We investigated a previously unidentified subaerial corticolous strain of the genus Elliptochloris TschermakWoess. The alga shares the generic morphological characters with Elliptochloris bilobata, the type species of the genus, but it has a thicker cell wall of adult globular cells, different chloroplast structure and it also differs in shape of elliptical autospores. The differences of the autospore shape between both species were evaluated using landmark-based geometric morphometrics. The 18S rDNA gene sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Phylogenies based on 18S have identified multiple clades within the Trebouxiophyceae, including the Chlorellales, Geminella , Oocystis , Prasiola , Microthamniales , Trebouxiales, Watanabea , Choricystis , and Ellipotochloris clades, as well as several other lineages consisting of a single species or genus (e.g., Pleurastrosarcina , Xylochloris , and Lobosphaera ). The relationship among these clades, however, was largely unresolved based on 18S data (Karsten et al, ; Eliáš et al, ; Darienko et al, ; Neustupa et al, , ; Bock et al, ).…”
Section: Chloroplast Phylogenomics Of Chlorophytamentioning
confidence: 99%
“…Phylogenies based on 18S have identified multiple clades within the Trebouxiophyceae, including the Chlorellales, Geminella , Oocystis , Prasiola , Microthamniales , Trebouxiales, Watanabea , Choricystis , and Ellipotochloris clades, as well as several other lineages consisting of a single species or genus (e.g., Pleurastrosarcina , Xylochloris , and Lobosphaera ). The relationship among these clades, however, was largely unresolved based on 18S data (Karsten et al, ; Eliáš et al, ; Darienko et al, ; Neustupa et al, , ; Bock et al, ).…”
Section: Chloroplast Phylogenomics Of Chlorophytamentioning
confidence: 99%
“…Pseudococcomyxa has only rarely been reported as the photobiont of lichen fungi (Muggia et al 2010), but this fact certainly reflects problems using morphology to distinguish Pseudococcomyxa from Coccomyxa, and recent work by Pröschold et al demonstrated that the authentic strain of P. simplex SAG 216-9a belongs within the genus Coccomyxa in the Elliptochloris clade (2011). On the other hand, some species from the genus Elliptochloris (for example, Elliptochloris bilobata Tsch.-Woess) are widely recognized as symbionts in lichens (Tschermak-Woess 1985) and as free-living algae of sub-aerial habitats (Eliáš et al 2008;Tsarenko 2011). Other species in the genus are recognized as photobionts in marine invertebrates (Letsch et al 2009) or as freeliving terrestrial algae (Ettl & Gärtner 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, subaerial microalgae from southeast Asian tropical rainforest habitats gained increased interest by a series of studies [10][11][12][13][14] which lead to the establishment of two new genera of green algae, Jenufa [13] and Xylochloris [14]. Both genera appeared as somehow distant to any known genera of green algae, despite a taxon sampling as large as possible that has been applied in the 18S rDNA sequence analyses of both studies.…”
Section: Introductionmentioning
confidence: 99%